Tuberculosis pneumonia, a typical presentation of pulmonary TB. - Ghaed; a J. Al-Ghizawi (Basrah Journal of Veterinary Research)
This study was carried out to see the pattern of pneumonic disease in Basrah general hospital in the two groups of patients, inpatients out patients and to see the extent of tuberculosis presented as pneumonia, not as atypical case of clinical and X-ray findings in the apices of lungs.